Extensive phosphorylation of Smoothened in Hedgehog pathway activation - Zhang, Chi (National Academy of Sciences, 2004)
The transmembrane protein Smoothened (Smo) is activated in response to the extracellular protein signal, Hedgehog (Hh), and transmits this state of pathway activity into the cell. Previous studies in Drosophila have correlated pathway activation with Smo accumulation and increased phosphorylation. Using immunopurification and mass spectrometry, we identify here 26 serine/threonine residues within the Smo C-terminal cytoplasmic tail that are phosphorylated in Hh-stimulated cells. By systematically substituting alanine or glutamic acid to block or simulate phosphorylation, we provide evidence for a functional role of collective phosphorylation of a subset of phosphoresidues in pathway activation. This role is indicated by the ability of altered Smo proteins to produce changes in transcription of Hh-responsive genes in vivo and in cultured cells. These altered Smo proteins also affect biochemical indicators of pathway activity, such as Smo accumulation and phosphorylation of other pathway components. The prevalence and arrangement of phosphoresidues within the Smo cytoplasmic tail at recognition sites for cAMP-dependent protein kinase and casein kinase 1 suggest a role for these kinases in Smo phosphorylation, and such a role is supported by the effects of manipulating kinase activities in cultured cells. Our studies confirm and extend previous studies showing a positive effect for cAMP-dependent protein kinase and uncover a positive role for casein kinase 1α in Hh pathway activation.